2016
DOI: 10.1590/1678-4499.283
|View full text |Cite
|
Sign up to set email alerts
|

Identification of variability for agronomically important traits in rice mutant families

Abstract: AbstrAct:The increase of yield potential in new rice (Oryza sativa L.) varieties has been a major challenge for genetic improvement.The generation of mutants, followed by their characterization, constitutes a great possibility to isolate and select genes and genotypes that present agronomic traits of interest. This study significance. The results show that there is genetic variability among the mutant families, suggesting that the mutagen EMS at 1.5% is effective for generating mutants for all assessed traits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
4
17
0
Order By: Relevance
“…According to Chaturvedi et al (2016) the development of chickpea varieties for their amenability to machine harvesting is one of the potential strategies to reduce cost of cultivation. The result obtained for the plant height was consistent with that obtained by Luz et al (2016) in rice mutant families. Luz et al (2016) has reported that among the characters scored, plant height was the most affected by the mutagen.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to Chaturvedi et al (2016) the development of chickpea varieties for their amenability to machine harvesting is one of the potential strategies to reduce cost of cultivation. The result obtained for the plant height was consistent with that obtained by Luz et al (2016) in rice mutant families. Luz et al (2016) has reported that among the characters scored, plant height was the most affected by the mutagen.…”
Section: Discussionsupporting
confidence: 88%
“…The result obtained for the plant height was consistent with that obtained by Luz et al (2016) in rice mutant families. Luz et al (2016) has reported that among the characters scored, plant height was the most affected by the mutagen. The reduction of plant height was also reported by Khan et al (2005) , Wani (2011) , and ( Kozgar, 2014 ) in chickpea mutant families.…”
Section: Discussionsupporting
confidence: 88%
“…This study confirms that genetic modification through mutation can improve agronomic and biomass performance (Figures 3-6). These findings agree with Luz et al (2016) who reported that EMS enhances agronomic performance of mutant rice families when compared to the non-mutagenized control families. EMS mutagenesis induces desirable changes in the gene structure, which produces mutants with altered agronomic traits such as increased spike length, tiller number, heavier kernel weight and biomass (Feldman et al, 2017;Mohapatra et al, 2014).…”
Section: Mean Performance For Biomass and Agronomic Traits Under Variable Drought Stresssupporting
confidence: 92%
“…In rice, mutants were developed from immature embryos (Ookawa et al, 2014), calli obtained from seeds (Serrat et al, 2014) and cell suspension cultures (Chen et al, 2013). Seeds are, however, easier to handle and do not require a specialized structure, and is therefore, the most widely used material (Da Luz et al, 2016;Oladosu et al, 2016). When seeds are mutagenized, it is important to standardize the seed mutagenic absorption through the pre-soaking of the seed in distilled water, since it also activates the seed metabolism and helps the mutagen action.…”
Section: Random Mutationsmentioning
confidence: 99%
“…However, spontaneous mutation rates in higher plants are low, ranging from 10 −5 to 10 −8 (Jiang and Ramachandran, 2010). Thus, mutagenesis is an important strategy to increase mutation frequency (Maluszynski et al, 2000; Da Luz et al, 2016) enabling studies of functional genomics and the development of new genotypes.…”
Section: Introductionmentioning
confidence: 99%